2019
DOI: 10.1111/bjdp.12299
|View full text |Cite
|
Sign up to set email alerts
|

The relative contribution of parenting practices in predicting trait emotional intelligence in an Italian adolescent sample

Abstract: This study examines the relationship between trait emotional intelligence (trait EI), support, and parental psychological control practices. Three hundred adolescents, between 11 and 13 years old, took part in the study (163 were males and 137 were females). Participants completed the Perceptions of Parents Scales for the parental support, the Dependency (DPC)-and Achievement (APC)-oriented Psychological Control Scales for the parental psychological control, and the Trait Emotional Intelligence Questionnaire-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 61 publications
1
6
0
3
Order By: Relevance
“…It is a six-item scale (e.g., "My mother/father listens to my opinion or perspective when I've got a problem") using a fivepoint Likert scale ranging from 1 (not at all true) to 5 (very true). Previous studies (Costa et al, 2016;Gugliandolo, Mavroveli, Costa, et al, 2019;Vansteenkiste et al, 2005) in different countries, including Italy, have used this scale successfully, showing good psychometric properties. In this study, the internal consistency was satisfactory (α =.84; see Table 1).…”
Section: Methodsmentioning
confidence: 95%
“…It is a six-item scale (e.g., "My mother/father listens to my opinion or perspective when I've got a problem") using a fivepoint Likert scale ranging from 1 (not at all true) to 5 (very true). Previous studies (Costa et al, 2016;Gugliandolo, Mavroveli, Costa, et al, 2019;Vansteenkiste et al, 2005) in different countries, including Italy, have used this scale successfully, showing good psychometric properties. In this study, the internal consistency was satisfactory (α =.84; see Table 1).…”
Section: Methodsmentioning
confidence: 95%
“…Rather, the construct involves dispositional variables deriving, for example, from childhood temperament [9,10], and genes [11]. Conversely, findings regarding the role of contextual variables on shaping children's TEI, like parenting styles [12], are rather mixed. Several researchers have found that children's TEI may impact on subsequent development of social and emotional issues (e.g., [13,14]).…”
Section: Introductionmentioning
confidence: 99%
“…Todavia, Gugliandolo et al, (2019) trazem que o período para os melhores resultados da Inteligência Emocional é na pré-adolescência, pois é normal na transição o adolescente perder a confiança em suas capacidades emocionais.…”
Section: Discussionunclassified
“…Para isso, os aspectos parentais que se destacaram como preditores positivos na Inteligência Emocional dos pré-adolescentes foram o apoio a autonomia materno e o envolvimento afetivo paterno (GUGLIANDOLO et al, 2019).…”
Section: Discussionunclassified
See 1 more Smart Citation